Integrative Study Supports the Role of Trehalose in Carbon Transfer From Fungi to Mycotrophic Orchid - Ponert, Jan; Šoch, Jan; Vosolsobě, Stanislav; Čiháková, Klára; Lipavská, Helena (Frontiers in plant science, 2021)
Orchids rely on mycorrhizal symbiosis, especially in the stage of mycoheterotrophic protocorms, which depend on carbon and energy supply from fungi. The transfer of carbon from fungi to orchids is well-documented, but the identity of compounds ensuring this transfer remains elusive. Some evidence has been obtained for the role of amino acids, but there is also vague and neglected evidence for the role of soluble carbohydrates, probably trehalose, which is an abundant fungal carbohydrate. We therefore focused on the possible role of trehalose in carbon and energy transfer. We investigated the common marsh orchid (Dactylorhiza majalis) and its symbiotic fungus Ceratobasidium sp. using a combination of cultivation approaches, high-performance liquid chromatography, application of a specific inhibitor of the enzyme trehalase, and histochemical localization of trehalase activity. We found that axenically grown orchid protocorms possess an efficient, trehalase-dependent, metabolic pathway for utilizing exogenous trehalose, which can be as good a source of carbon and energy as their major endogenous soluble carbohydrates. This is in contrast to non-orchid plants that cannot utilize trehalose to such an extent. In symbiotically grown protocorms and roots of adult orchids, trehalase activity was tightly colocalized with mycorrhizal structures indicating its pronounced role in the mycorrhizal interface. Inhibition of trehalase activity arrested the growth of both symbiotically grown protocorms and trehalose-supported axenic protocorms. Since trehalose constitutes only an inconsiderable part of the endogenous saccharide spectrum of orchids, degradation of fungal trehalose likely takes place in orchid mycorrhiza. Our results strongly support the neglected view of the fungal trehalose, or the glucose produced by its cleavage as compounds transported from fungi to orchids to ensure carbon and energy flow. Therefore, we suggest that not only amino acids, but also soluble carbohydrates are transported. We may propose that the soluble carbohydrates would be a better source of energy for plant metabolism than amino acids, which is partially supported by our finding of the essential role of trehalase.
Keywords: mycotrophy; carbon transfer; trehalose; orchid; histochemical localization; carbohydrate; trehalase; mycorrhiza